Dual-functional carbon-doped polysilicon films for passivating contact solar cells: regulating physical contacts while promoting photoelectrical properties. Issue 12 (27th October 2021) - Lin, Yiran; Yang, Zhenhai; Liu, Zunke; Zheng, Jingming; Feng, Mengmeng; Zhi, Yuyan; Lu, Linna; Liao, Mingdun; Liu, Wei; Ma, Dian; Han, Qingling; Cheng, Hao; et al.
Abstract : Blistering-free poly-films were achieved by introducing carbon impurities, showing a proof-of-concept certified efficiency of 23.82% based on n-Si/SiO x /poly-Si contacts. Abstract : Passivating contact crystalline silicon solar cells are among the most promising industrially feasible photovoltaic (PV) technologies and require excellent physical contacts to handle device performance. Here, we report a versatile polysilicon (poly-Si) film intentionally doped with carbon (C) to suppress blistering and improve physical contacts. Our investigations of blistering mechanisms reveal that the reduced crystallization fraction of poly-Si in conjunction with the suppressed level of hydrogen release should primarily be responsible for the blistering-free appearance of the C-doped poly-Si films. Moreover, additional advantages of high-quality passivation with a high implied open-circuit voltage (i V oc ) exceeding 750 mV and an excellent optical response in the infrared band with a net current-density gain of 0.31 mA cm −2 are endowed to the C-doped poly-Si films. Consequently, the proof-of-concept devices featuring C-doping show a champion efficiency of 24.27%, which is 1.18% higher than that of the C-free counterparts (23.09%). Also, we present a certified efficiency of 23.82%, suggesting that the C-doped poly-Si has the potential to achieve high-efficiency c-Si solar cells.